Microencapsulated Nigella sativa L. oil as functional ingredient for non-dairy creamer - Mohammed, Nameer Khairullah (2018)
The main objective of this research was to produce Nigella sativa oil (NSO) based non-dairy creamer (NDC) via microencapsulation and agglomeration process. Two extraction methods namely, supercritical fluid extraction (SFE) and cold press (CP) were used to extract the oil from Nigella sativa seed. The microencapsulation using spray dryer was used and the effectiveness of three different independent variables namely, oil concentration (10-30%), wall materials content (10-30%) and inlet air temperature (150-190ºC) were optimized using response surface methodology (RSM). The effects of accelerated storage time (24 days) at 65ºC on the stability of microencapsulated Nigella sativa oil (MNSO) compared to the NSO without encapsulation were evaluated. Total oil was recovered from the powder of MNSO and evaluated in every 6 days along with the NSO. Optimization of the fluidized bed dryer process conditions in terms of drying time (20-60 min), drying temperature (20-50ºC) and feed flow rate (1-2.5 mL/min) were conducted using RSM to obtain the non-dairy creamer (NDC) by agglomeration the microencapsulated oil. The NDC was characterized based on antioxidant activity and physical properties. It was found that the oil obtained by SFE showed high content of thymoquinone (TQ) and total phenolic content (TPC) compared to the oil obtained by CP. In addition, antioxidant activity measured by DPPH and ferric reducing antioxidant power (FRAP) activity showed higher activity for SFE oil. The optimal conditions of microencapsulation were 30% wall material, 10% concentration of oil, and 160°C drying inlet air temperature. The properties of oil without encapsulation has undergone many changes with a reduction in oxidative stability, bioactive compounds content, antioxidant activity, and fatty acid composition alteration. Microencapsulated oil indicated a higher stability and resistance under the same storage conditions. The optimum conditions of the fluidized bed agglomeration were: inlet air temperature (50ºC), drying time (25 min), and feed flow rate (1 mL/min). This process resulted in further improvement of the powder properties with high solubility, particle size, and glass transition temperature (Tg), as well as lower moisture content, water activity (aw), wettability, hygroscopicity, and bulk density compared to the spray dried powder with acceptable results of sensory evaluation. In conclusion, the SFE represents suitable method for NSO. The encapsulation extended the shelf life of the NSO and the agglomeration improved the instant properties and palatable taste. The developed NSO-based NDC can be used as an alternative to the saturated fat and/or hydrogenated oils based NDC.